Smart City Components in Tbilisi - Khutsishvili, Levan (Politics / პოლიტიკა; 2018: მესამე ნომერი, 2018)
Article concentrates on reasons of urbanization and problems that has been appeared in cities during the process of mass urbanization. Challenges that cities are facing are related with infrastructural, socio-economic, political, environmental issues. To deal with new reality, it became necessary to create new concepts of urban development, that will guarantee the sustainable future of the urban areas. Article underlines the importance of one of the urban concepts – “Smart City”, development, structure and components of the concept. Article also speaks about the achievements of Tbilisi according to the concept of  “Smart City”.
Keywords: Smart City, Tbilisi, Urban Development, Urbanization, Life Quality